INVESTIGASI PENGARUH VARIASI AIR LAUT TERHADAP LAJU KOROSI BAJA ST 37 - Djahilepang, Raywantus Baur; Suprapto, Agus; Tsamroh, Dewi Izzatus (RING ME, 2024)
In the current era of globalization, metal has an important role and is a primary need in various aspects of human daily life. One metal that is widely used is steel, which is a mixture of iron (Fe) and carbon (C) with the addition of other ingredients in the modern context. Low carbon steel, such as ST 37, is often used in making components such as nails, bolts and screw threads. The affordability and availability of ST 37 makes it a top choice in the construction industry, although it is often subject to corrosion problems due to its natural properties. In various situations and conditions, the wide use of ST 37 steel often interacts with natural elements, such as sea water, river water, oxygen, pH values, and other environmental conditions. The problem of corrosion is a major concern for many researchers and industry, because it can affect various processes such as cleaning by etching, pickling, and the use of corrosive chemicals such as acids and salts to inhibit corrosion. The test results showed that the highest corrosion rate occurred in Tanjung Perak Surabaya sea water, amounting to 2.817 mpy, while Panjang Pasuruan sand sea water had the lowest corrosion rate of 0.626 mpy.